Is uterine artery embolisation a safe and effective modality to treat submucosal fibroids? - Rayhab Mashal; Neeral Patel; Bhavna Pitrola; Thomas Sewell; Asmaa Al-Kufaishi; Shabnam Taheri; Mohamad Hamady (CVIR Endovascular)
Highlights • Uterine fibroid embolization (UFE) reduced the median volume of dominant submucosal leiomyomas by 64% and achieved over 90% devascularization in 94.8% of cases. • High patient satisfaction was observed, with 84.5% of patients successfully discharged without needing further intervention. • Severe adverse events were rare, affecting only 3.2% of patients, with pelvic infections being the most significant. • Mild adverse events occurred in 16.8% of patients, including infections requiring antibiotics and persistent vaginal discharge. • A multidisciplinary approach is essential for managing patients with submucosal leiomyomas undergoing UFE to ensure optimal treatment outcomes.